2020
DOI: 10.5398/tasj.2020.43.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Utilizations and Intestinal Morphology of Broilers Treated with Lactobacillus plantarum AKK30 – Oligosaccharides Synbiotic

Abstract: Lactobacillus plantarum AKK30 inoculum in de Maan Rogosa Sharpe Broth (MRSB) grown on media containing oligosaccharides (inulin or mannan oligosaccharides/MOS) was studied in vitro and in vivo. In vitro assay was conducted to characterize metabolite profiles and its effect on pathogenic bacteria, while in vivo assay was conducted to study the metabolic energy, nitrogen retention, and intestinal morphology of broilers. A total of 24 male broilers-40-day-old (average body weight= 1.725±0.05 kg) strains Cobb-500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…One possibility is that zinc purposes as a modulator of the immune response in chicken, leading to a stronger intestinal mucosa and improved feed efficiency. The chicken's intestine plays a vital role in facilitating the absorption of nutrients into its body [33]. As such, the health of the intestine is a critical factor in optimizing FCR and evaluating the chicken's overall performance.…”
Section: Feed Conversion Ratiomentioning
confidence: 99%
“…One possibility is that zinc purposes as a modulator of the immune response in chicken, leading to a stronger intestinal mucosa and improved feed efficiency. The chicken's intestine plays a vital role in facilitating the absorption of nutrients into its body [33]. As such, the health of the intestine is a critical factor in optimizing FCR and evaluating the chicken's overall performance.…”
Section: Feed Conversion Ratiomentioning
confidence: 99%
“…[ 15 ] reported that the use of inulin as a prebiotic increased the viability of Lactobacillus plantarum . Synbiotics (a mixture of inulin and L. plantarum ) evidently inhibited the proliferation of pathogenic bacteria [ 16 ] and improved intestinal morphology, metabolizable energy, and nitrogen retention [ 17 ]. The improvement of intestinal morphology increases nutrient absorption, thereby improving physical quality and reducing the egg cholesterol content [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, inulin derived from gembili was combined with L. plantarum Ina CC B76. Although synbiotics (based on inulin and gembili tubers and L. plantarum ) have been used in broilers [ 17 , 24 , 25 ], to the best of the authors’ knowledge, they have never been used in ducks, especially in the late production phase.…”
Section: Introductionmentioning
confidence: 99%